Nationalism in Eastern Europe - Bollerup, S. author. aut Link
XX, 308 p.
Keywords: Nationalism in Eastern Europe offers a thorough application of theories of nationalism in an analysis of the recent national revivals and conflicts in Eastern Europe. The book discusses both microsociological theories from social psychology and economics and macrosociological theories from sociology and political science. In a comprehensive comparative analysis these theories are applied to the late-Twentieth-century experiences of Estonia, Moldova, Croatia and the former Czechoslovakia. In doing so, the authors arrive at generalizable explanations of both the prevalence and the potential fatality of nationalism.